2020
DOI: 10.1111/bdi.13017
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of suicidal behavior in bipolar disorder

Abstract: Background Excess mortality is a critical hallmark of bipolar disorder (BD) due to co‐occurring general medical disorders and especially from suicide. It is timely to review of the status of suicide in BD and to consider the possibility of limiting suicidal risk. Methods We carried out a semi‐systematic review of recent research reports pertaining to suicide in BD. Findings Suicide risk in BD is greater than with most other psychiatric disorders. Suicide rates (per 100,000/year) are approximately 11 and 4 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 89 publications
2
30
0
1
Order By: Relevance
“…Among psychiatric disorders, bipolar disorder (BD) has the highest suicide incidence ( 1 4 ). A recent meta-analysis demonstrated that the lifetime prevalence of suicide attempts (SA) in BD was 33.9% ( 5 ), which is at least 20 times higher than the general population ( 6 ). Epidemiological studies also showed that approximately 20–60% of BD patients had attempted suicide in their lifetime, and approximately 4–19% died due to suicide ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among psychiatric disorders, bipolar disorder (BD) has the highest suicide incidence ( 1 4 ). A recent meta-analysis demonstrated that the lifetime prevalence of suicide attempts (SA) in BD was 33.9% ( 5 ), which is at least 20 times higher than the general population ( 6 ). Epidemiological studies also showed that approximately 20–60% of BD patients had attempted suicide in their lifetime, and approximately 4–19% died due to suicide ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, suicide prevention is extremely important, as MDD and BD are high‐risk factors for suicidal thoughts or behaviors in psychiatric patients. 19 , 29 , 30 …”
Section: Description Of Targeted Psychiatric Disordersmentioning
confidence: 99%
“…Moreover, suicide prevention is extremely important, as MDD and BD are high-risk factors for suicidal thoughts or behaviors in psychiatric patients. 19,29,30 Autism spectrum disorder is characterized by difficulty with social communication, repetitive behavior, and highly restricted interests or activities. 31 Four separate disorders, including autistic disorder, childhood disintegrative disorder, Asperger syndrome, and pervasive developmental disorder, were integrated into the single entity of ASD in DSM-5.…”
Section: Description Of Targeted Psychiatric Disordersmentioning
confidence: 99%
“…Of note, a recent multicentric large-sample Italian study identified an earlier age at first contact with psychiatric services and the presence of psychotic symptoms or hospitalizations in the last year among the factors associated with suicidal behavior in bipolar patients [ 21 ]. On the other hand, the identification of the clinical variables predicting self-harm in BD is extremely important to establish proper treatment with anti-suicidal compounds such as lithium [ 22 , 23 ]. Therefore, many studies have been recently undertaken to better understand the pathophysiology of suicide attempts in BD as well as to identify potential peripheral markers of suicidal behavior, with the scope of developing preventive strategies and identifying effective drugs.…”
Section: Introductionmentioning
confidence: 99%